2005
DOI: 10.1161/01.cir.0000151812.86142.45
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Differentiate into an Endothelial Phenotype, Enhance Vascular Density, and Improve Heart Function in a Canine Chronic Ischemia Model

Abstract: Background-Bone marrow-derived stem cells are under investigation as a treatment for ischemic heart disease.Mesenchymal stem cells (MSCs) have been used preferentially in the acute ischemia model; data in the chronic ischemia model are lacking. Methods and Results-Twelve dogs underwent ameroid constrictor placement. Thirty days later, they received intramyocardial injections of either MSCs (100ϫ10 6 MSCs/10 mL saline) (nϭ6) or saline only (10 mL) (controls) (nϭ6). All were euthanized at 60 days. Resting and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
484
4
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 710 publications
(516 citation statements)
references
References 33 publications
19
484
4
9
Order By: Relevance
“…In skin cells, endothelial cells, pericytes, monocytes/macrophage, and adipocytes have been reported (24,25). However, it is currently unknown whether MSCs can differentiate into keratinocytes.…”
Section: Cultured Mscs Express Keratin14mentioning
confidence: 99%
“…In skin cells, endothelial cells, pericytes, monocytes/macrophage, and adipocytes have been reported (24,25). However, it is currently unknown whether MSCs can differentiate into keratinocytes.…”
Section: Cultured Mscs Express Keratin14mentioning
confidence: 99%
“…Several cell sources have been identified and investigated for the purpose of cardiac regeneration. Some of the extensively investigated cell types include bone marrow-derives adult stem cells [7,8] and embryonic stem cells [9][10][11]. Some of the other cell types that carry some doubts in terms of their capability for the purpose of myocardial regeneration are the adipose-derived adult stem cells [12,13] and the adult skeletal myoblasts [14].…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 99%
“…We and others have shown that when human MSCs are grown in endothelial differentiation medium, they express endothelial markers such as CD31, von Willebrand factor and VEcadherin, both at the mRNA and protein level [11][12][13][14][15][16][17]. In addition, the actively take up acidic LDL, another hallmark of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%